2014
DOI: 10.1152/japplphysiol.00309.2013
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between gastrocnemius medialis fascicle and Achilles tendon compliance: a new insight on the quick-release method

Abstract: The insufficient temporal resolution of imaging devices has made the analysis of very fast movements, such as those required to measure active muscle-tendon unit stiffness, difficult. Thus the relative contributions of tendon, aponeurosis, and fascicle to muscle-tendon unit compliance remain to be determined. The present study analyzed the dynamic interactions of fascicle, tendon, and aponeurosis in human gastrocnemius medialis during the first milliseconds of an ankle quick-release movement, using high-frame-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 57 publications
2
21
1
Order By: Relevance
“…After each extension, the knee was passively placed in starting position. The previous studies showed higher maximal joint velocity during unloaded plantar flexions performed with preactivation (1325° s −1 , Farcy et al 2014) compared to without pre-activation (701° s −1 , Hauraix et al 2015). However, the maximal fascicle shortening velocity was much higher without pre-activation (23.2 cm s −1 compared to 34.7 cm s −1 ).…”
Section: Protocolmentioning
confidence: 83%
“…After each extension, the knee was passively placed in starting position. The previous studies showed higher maximal joint velocity during unloaded plantar flexions performed with preactivation (1325° s −1 , Farcy et al 2014) compared to without pre-activation (701° s −1 , Hauraix et al 2015). However, the maximal fascicle shortening velocity was much higher without pre-activation (23.2 cm s −1 compared to 34.7 cm s −1 ).…”
Section: Protocolmentioning
confidence: 83%
“…We deliberately chose to perform plantar-flexion contractions without preactivation so as not to be in a "quick-release" condition. Indeed, although such an experimental setup should induce an increase in angular velocity, quick-release movements largely increase the contribution of tendinous structures (17) and should notably alter the fascicle-tendon interaction (and length) at the beginning of the contraction. Consequently, these authors reported a lower maximal gastrocnemius medialis fascicle-short-ening velocity in the quick-release condition than in the present study in NLc [4.6 L O /s (17)].…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…The torque measured by the isokinetic dynamometer was corrected for inertia and gravity to obtain external torque at the ankle joint. On the specific ergometer system (light-load isoinertial conditions), the moment of inertia (i.e., foot, footplate, and additional loads) was estimated using quick-release protocol (17). Torque was calculated as the moment of inertia multiplied by the acceleration of the ankle angle and corrected for weight (foot and additional loads).…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…1c). When the fascicle was not fully visible, its length (L F ) was interpolated as the length of the straight line between the superficial and deep aponeurosis (Hauraix et al 2013, Farcy et al 2014. The angle between the fascicle and the deep aponeurosis corresponded to the pennation angle.…”
Section: Data Processing During Eccentric Exercisementioning
confidence: 99%